2022
DOI: 10.1097/md.0000000000030172
|View full text |Cite
|
Sign up to set email alerts
|

Research hotspots and trends of multimodality MRI on vascular cognitive impairment in recent 12 years: A bibliometric analysis

Abstract: Background: Multimodality magnetic resonance imaging (MRI) is widely used to detect vascular cognitive impairment (VCI). However, a bibliometric analysis of this issue remains unknown. Therefore, this study aimed to explore the research hotspots and trends of multimodality MRI on VCI over the past 12 years based on the Web of Science core collection using CiteSpace Software (6.1R2). Methods: Literature related to multimodality MRI for VCI from 2010 to 2021 was identified and analyzed from the Web of Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Many studies have reported extensive changes in the GMV in patients with VCI, covering the frontal and temporal cortices, pons, thalamus, caudate nucleus, and hippocampus. [ 19 , 20 ] He study [ 21 ] showed that GMV in multiple subregions of the hippocampus is generally reduced in patients with VCI, and there is a significant correlation between GMV changes in these brain regions and specific clinical scale scores. [ 21 ] Specific changes in brain structure in VCI have been discussed from the point of view of brain morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported extensive changes in the GMV in patients with VCI, covering the frontal and temporal cortices, pons, thalamus, caudate nucleus, and hippocampus. [ 19 , 20 ] He study [ 21 ] showed that GMV in multiple subregions of the hippocampus is generally reduced in patients with VCI, and there is a significant correlation between GMV changes in these brain regions and specific clinical scale scores. [ 21 ] Specific changes in brain structure in VCI have been discussed from the point of view of brain morphology.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, despite the large number of MRI publications from Arab countries, none appear among the list of the most productive or impactful countries in global bibliometric analyses of MRI research [ 65 , 66 ]. There are several recommendations for future researchers to enhance the productivity and impact of MRI research in Arab countries to reach the global figure.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is an important tool and method in the study of recognition, and it is of great significance in the diagnosis of AD with the aid of MRI. Structural MRI can explore the underlying pathophysiology through histopathology (Reijmer and Van Veluw, 2016 ), and functional magnetic resonance imaging (fMRI) can be used to detect brain function in patients (Yang et al, 2015 ), multimodal MRI is widely used to detect vascular cognitive impairment (Xia et al, 2022 ). Rs-fMRI can detect leukoaraiosis and a wide range of brain dysfunction (Cheng et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of highintensity MRI in WM and biomarkers such as neurofilament chain and glial fibrillary acidic protein revealed that serum GFAP is a promising fluid biomarker because it is associated not only with clinical severity but also with cognitive function (Huss et al, 2022). Ford et al (2022) found that blood-brain barrier dysfunction is a hallmark of aging and aging-related diseases, including small vessel disease of the brain and AD. A novel biomarker of blood-brain barrier dysfunction is the blood-brain barrier water exchange rate [k(W)], as measured by diffusionweighted arterial spin labeling (DW-ASL) MRI (Ford et al, 2022).…”
Section: Hotspots and Research Status On Mri Of Wm In Admentioning
confidence: 99%